Kalibrasi Peralatan Navigasi Penerbangan Dalam Mengantisipasi Keselamatan Penerbangan - Rosidin Syamsudin (WARTA ARDHIA, 2010)
Flight safety is a major factor that needs attention not only from the government as a regulator but the organizers airport as infrastructure providers, and airlines as the airport service users.Facilities/ flights operated navigation equipment at the airport for flight navigation services shall be calibrated periodically to keep it operating feasibility (accurate). Facilities / aviation navigation equipment consists of telecommunications facilities, aviation, aeronautical information facilities and amenities aviation meteorological information.